Mekanisme Pembubaran Partai Politik: Perbandingan Indonesia dan Turki - Baharuddin Riqiey (PLEDOI (Jurnal Hukum dan Keadilan), 2024)
Political parties are not sacred, so they can be dissolved according to the provisions of the applicable laws. The mechanism for dissolving political parties in each country is certainly different. So this research aims to examine the differences in mechanisms for the dissolution of political parties in Indonesia and Turkey. This research is legal research with a statutory and conceptual approach. The results of this research show that the mechanism for dissolving political parties in Indonesia and Turkey is both submitted to the Constitutional Court. Still, specifically for Turkey, it must go through the Court of Cassation first. The applicant who can apply for the dissolution of a political party in Indonesia is the Government which can be represented by the Attorney General and/or the Minister assigned by the President while in Turkey the person who can apply is the Chief Public Prosecutor. The reasons for the dissolution of political parties in Indonesia are because (i) the ideology, principles, objectives, and programs of political parties conflict with the 1945 Constitution of the Republic of Indonesia; (ii) carrying out activities that endanger the integrity and safety of the Republic of Indonesia; and (iii) adhere to, develop and spread the teachings or understanding of communism/Marxism-Leninism. Meanwhile, the reasons for the dissolution of political parties in Turkey are: (i) the statutes and programs, as well as the activities of political parties be contrary to the independence of the State, its indivisible integrity with its territory and nation, human rights, the principles of equality and rule of law, sovereignty of the nation, the principles of the democratic and secular republic; (ii) aim to promote or establish class or group dictatorship or dictatorship of any kind, nor shall they incite citizens to crime; and (iii) receive financial assistance from abroad.